Enzymatic hydrolysis of silkworm pupa and its allergenicity evaluation by animal model with different immunization routes - Yan Dai; Meijia Huang; Yujuan Xu; Lixia Mu; Jingyan Gao; Hongbing Chen; Zhihua Wu; Anshu Yang; Yong Wu; Xin Li (Food Science and Human Wellness)
Silkworm pupa is a nourishing food with high nutritional value, but its consumption has been greatly limited given its allergenicity. Enzyme hydrolytic technique is recognized as an effective method to reduce the allergenicity of protein. In this study, we aimed to investigate the effect of enzymolysis on the allergenicity of silkworm pupa. Crude silkworm pupa protein was extracted through alkali extraction and acid precipitation, which included 5 proteins with the molecular weights ranging from 34 kDa to 76 kDa, and silkworm pupa were then hydrolyzed by alkaline protease. The allergenicity of silkworm pupa protein and its enzymatic hydrolysates was evaluated by establishing BALB/c mice model, and the mice were immunized via intragastric gavage and intraperitoneal injection, respectively. The results indicated that the intraperitoneal injection immunization route induced more by detecting with antibodies, histamine and Th2-related cytokines. Moreover, mice treated with silkworm pupa protein peptide displayed no obvious allergic symptoms, indicating that enzyme hydrolytic technique could significantly reduce the allergenicity of silkworm pupa.